Common gene variants within 3′‐untranslated regions as modulators of multiple myeloma risk and survival. Issue 8 (20th November 2020) - Melaiu, Ombretta; Macauda, Angelica; Sainz, Juan; Calvetti, Diego; Facioni, Maria Sole; Maccari, Giuseppe; ter Horst, Rob; Netea, Mihai G.; Li, Yang; Grząśko, Norbert; Moreno, Victor; Jurczyszyn, Artur; et al.
Abstract: We evaluated the association between germline genetic variants located within the 3′‐untranlsated region (polymorphic 3′UTR, ie, p3UTR) of candidate genes involved in multiple myeloma (MM). We performed a case‐control study within the International Multiple Myeloma rESEarch (IMMEnSE) consortium, consisting of 3056 MM patients and 1960 controls recruited from eight countries. We selected p3UTR of six genes known to act in different pathways relevant in MM pathogenesis, namely KRAS (rs12587 and rs7973623), VEGFA (rs10434), SPP1 (rs1126772), IRF4 (rs12211228) and IL10 (rs3024496). We found that IL10‐ rs3024496 was associated with increased risk of developing MM and with a worse overall survival of MM patients. The variant allele was assayed in a vector expressing eGFP chimerized with the IL10 3′‐UTR and it was found functionally active following transfection in human myeloma cells. In this experiment, the A‐allele caused a lower expression of the reporter gene and this was also in agreement with the in vivo expression of mRNA measured in whole blood as reported in the GTEx portal. Overall, these data are suggestive of an effect of the IL10‐ rs3024496 SNP on the regulation of IL10 mRNA expression and it could have clinical implications for better characterization of MM patients in terms of prognosis. Abstract : What's new? The polymorphic 3′‐untranslated region (p3UTR) has been shown to affect gene expression and lead to differential predisposition or prolonged survival in a variety of cancer types. Here, the authors evaluate the association between germline genetic variants within the p3UTR of candidate genes involved in multiple myeloma. The results show that IL10 ‐rs3024496 might affect immune homeostasis through the modulation of IL10 mRNA expression. Overall, the findings suggest that the inclusion of personal genetic background information into the clinical evaluation criteria could help to improve the stratification of patients with multiple myeloma in terms of risk progression and prognosis.